XUV-Initiated Dissociation Dynamics of Molecular Oxygen (O2) - Rebholz, Marc; Ding, Thomas; Aufleger, Lennart; Hartmann, Maximilian; Meyer, Kristina; Stooß, Veit; Magunia, Alexander; Wachs, David; Birk, Paul; Mi, Yonghao; Borisova, Gergana Dimitrova; da Costa Castanheira, Carina; et al. (My University, 2021)
We performed a time-resolved spectroscopy experiment on the dissociation of oxygen molecules after the interaction with intense extreme-ultraviolet (XUV) light from the free-electron laser in Hamburg at Deutsches Elektronen-Synchrotron. Using an XUV-pump/XUV-probe transient-absorption geometry with a split-and-delay unit, we observe the onset of electronic transitions in the O2+ cation near 50 eV photon energy, marking the end of the progression from a molecule to two isolated atoms. We observe two different time scales of 290 ± 53 and 180 ± 76 fs for the emergence of different ionic transitions, indicating different dissociation pathways taken by the departing oxygen atoms. With regard to the emerging opportunities of tuning the central frequencies of pump and probe pulses and of increasing the probe–pulse bandwidth, future pump–probe transient-absorption experiments are expected to provide a detailed view of the coupled nuclear and electronic dynamics during molecular dissociation.